Vascular peroxidase 1 mediates hypoxia-induced pulmonary artery smooth muscle cell proliferation, apoptosis resistance and migration - You, Baiyang; Liu, Yanbo; Chen, Jia; Huang, Xiao; Peng, Huihui; Liu, Zhaoya; Tang, Yixin; Zhang, Kai; Xu, Qian; Li, Xiaohui; Cheng, Guangjie; Shi, Ruizheng; et al. (Cardiovascular research, 2018)
Abstract Aims Reactive oxygen species (ROS) play essential roles in the pulmonary vascular remodelling associated with hypoxia-induced pulmonary hypertension (PH). Vascular peroxidase 1 (VPO1) is a newly identified haeme-containing peroxidase that accelerates oxidative stress development in the vasculature. This study aimed to determine the potential role of VPO1 in hypoxia-induced PH-related vascular remodelling. Methods and results The vascular morphology and VPO1 expression were assessed in the pulmonary arteries of Sprague-Dawley (SD) rats. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 4 (NOX4) and VPO1 expression and HOCl production were significantly increased in hypoxic rats, which also exhibited obvious vascular remodelling. Furthermore, a hypoxia-induced PH model was generated by exposing primary rat pulmonary artery smooth muscle cells (PASMCs) to hypoxic conditions (3% O2, 48 h), which significantly increased the expression of NOX4 and VPO1 and the production of HOCl. These hypoxic changes were accompanied by enhanced proliferation, apoptosis resistance, and migration. In PASMCs, hypoxia-induced changes, including effects on the expression of cell cycle regulators (cyclin B1 and cyclin D1), apoptosis-related proteins (bax, bcl-2, and cleaved caspase-3), migration promoters (matrix metalloproteinases 2 and 9), and NF-κB expression, as well as the production of HOCl, were all inhibited by silencing VPO1 with small interfering RNAs. Moreover, treatment with HOCl under hypoxic conditions upregulated NF-κB expression and enhanced proliferation, apoptosis resistance, and migration in PASMCs, whereas BAY 11-7082 (an inhibitor of NF-κB) significantly inhibited these effects. Conclusion Collectively, these results demonstrate that VPO1 promotes hypoxia-induced proliferation, apoptosis resistance, and migration in PASMCs via the NOX4/VPO1/HOCl/NF-κB signalling pathway.